Measuring The Competence of Human Resources in The Organization - Garaika Garaika (Komunitas Dosen Indonesia, 2021)
An organization can run effectively if the management functions such as planning, organizing, motivating and controlling in it are functioning properly, and the supporting elements are available and meet the requirements. One of the most important elements that can support the running of the company is human resources (employees). Human resources have an important role in determining the success of the organization. For that we need a tool for measuring employee performance results, so we look for criteria and weights to calculate the results of employee performance achievements, as a measure to calculate achievements using the analytical hierarchy process (AHP) method approach